Nonalcoholic Fatty Liver Disease Is Associated with Benign Prostate Hyperplasia - Chung, Goh Eun (J Korean Med Sci, 2020)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is associated with a wide spectrum of metabolic abnormalities. This study aimed to evaluate whether NAFLD is associated with benign prostatic hyperplasia (BPH) independent of other risk factors. METHODS: A total of 3,508 subjects who underwent prostate and hepatic ultrasonography were enrolled. NAFLD was diagnosed and graded by ultrasonographic findings. BPH was defined by total prostate volume. RESULTS: The prevalence of BPH was significantly increased according to NAFLD severity (P < 0.001). The multivariate analysis showed that NAFLD was associated with a 22% increase in the risk of BPH (odds ratio [OR], 1.22; 95% confidence interval [CI], 1.02–1.45). In non-obese subjects, NAFLD was associated with a 41% increase in the risk of BPH (OR, 1.41; 95% CI, 1.14–1.73), and an incremental increase in the risk of BPH according to NAFLD severity was pronounced (adjusted OR [95% CI], 1.32 [1.05–1.68] for mild NAFLD, 1.55 [1.15–2.10] for moderate to severe NAFLD vs. no NAFLD, P for trend = 0.004). However, in the obese population, the association of NAFLD in the risk of BPH was insignificant (P = 0.208). CONCLUSION: NAFLD is associated with an increased risk of BPH regardless of metabolic syndrome, especially in non-obese subjects. An incrementally increased risk of BPH according to NAFLD severity is prominent in non-obese subjects with NAFLD. Thus, physicians caring for non-obese patients with NAFLD may consider assessing the risk of BPH and associated urologic conditions.